2015
DOI: 10.1007/s11295-015-0847-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic versus environmental contributions to variation in seedling resprouting in Nothofagus obliqua

Abstract: Resprouting is an almost universal functional trait in temperate angiosperms and confers persistence at an individual level after the loss of above-ground biomass. The importance of genetic versus environmental sources of intraspecific variation in resprouting traits is largely unknown. We conducted two genetic field trials, 400 m apart in altitude, in order to sequentially assess seedling resprouting in four environmentally contrasting Argentinean populations of Nothofagus obliqua Mirb. (Oerst). We also perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
1
0
1
Order By: Relevance
“…Within a provenances trial, LE individuals showed lower height, although exhibiting high relative growth rates (Azpilicueta et al 2014). Meanwhile, in a study of the intraspecific variation of the resprouting capacity of N. obliqua species, LE was found to differ from other Argentinean populations in several key traits (Aparicio et al 2015). For example, LE had the lowest rate of investment in shoot per unit of root seedling biomass; it showed the lowest capacity for recovering height, in a trade-off with multiple resprouting and the highest degree of episodic frost tolerance during resprouting.…”
Section: Introductionmentioning
confidence: 89%
“…Within a provenances trial, LE individuals showed lower height, although exhibiting high relative growth rates (Azpilicueta et al 2014). Meanwhile, in a study of the intraspecific variation of the resprouting capacity of N. obliqua species, LE was found to differ from other Argentinean populations in several key traits (Aparicio et al 2015). For example, LE had the lowest rate of investment in shoot per unit of root seedling biomass; it showed the lowest capacity for recovering height, in a trade-off with multiple resprouting and the highest degree of episodic frost tolerance during resprouting.…”
Section: Introductionmentioning
confidence: 89%
“…de Sudamérica. Aparicio et al (2015) encontraron en un ensayo de orígenes de N. obliqua que la población de mayor altitud fue la menos afectada por una helada tardía de comienzos de verano y a la vez la de menor crecimiento en altura.…”
Section: Poblaciónunclassified